What are the health risks of occupational silver exposure?. Issue 7 (July 2018) - Ashna, Baheer; Madlon‐Kay, Diane J.
Abstract : EVIDENCE‐BASED ANSWER : Occupational silver exposure is associated with elevated blood and urine silver levels, decreased creatinine clearance irrespective of blood silver levels, complaints of respiratory symptoms, epistaxis, and decreased night vision. Workers may also have burns, abdominal pain, and argyria (SOR: B, case‐control study and case series)